PPS / PPE composite material and preparation method and application thereof

CN119708844BActive Publication Date: 2026-11-03KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411963100.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2026-11-03
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

PPS and PPE are incompatible, resulting in low elongation at break of the material. After mixing, they cannot be continuously extruded and molded, and carbonization points are generated during processing, affecting the quality of the material.

Method used

Graft copolymers with specific main chains and side chains, including graft copolymers with polyethylene, polypropylene, etc. as the main chain and polystyrene, etc. as the side chain, are used to improve the compatibility of PPS and PPE and reduce the formation of carbonization points during processing.

Benefits of technology

It improves the heat resistance and elongation at break of PPS/PPE composite materials, reduces the number of carbonization points, and enhances the processing quality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217663700000061
    Figure BDA0005217663700000061
  • Figure BDA0005217663700000071
    Figure BDA0005217663700000071
  • Figure BDA0005217663700000072
    Figure BDA0005217663700000072
Patent Text Reader

Abstract

The application discloses a PPS / PPE composite material and a preparation method and application thereof, and relates to the technical field of engineering plastics. The application provides a PPS / PPE composite material, which comprises the following components in parts by weight: 50-90 parts of a polyphenylene sulfide resin, 5-20 parts of a polyphenylene ether resin and 3-10 parts of a graft copolymer; wherein the graft copolymer comprises a main chain and a side chain; the main chain is one of a polyethylene, a polypropylene, an ethylene copolymer and a propylene copolymer; and the side chain is one of a polystyrene and a styrene copolymer; and the polyphenylene sulfide resin has a pH value of 5-8. The graft copolymer with the specific main chain and the side chain is used, so that the PPS / PPE composite material with good heat resistance, high elongation at break and few carbonization points is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of engineering plastics technology, and in particular to a PPS / PPE composite material, its preparation method, and its application. Background Technology

[0002] Polyphenylene sulfide (PPS) resin possesses advantages such as high temperature resistance, corrosion resistance, radiation resistance, flame retardancy, non-toxicity, excellent mechanical and electrical properties, and good dimensional stability of finished products, making it suitable for high-temperature resistant pipes. Polyphenylene ether (PPE) resin exhibits good mechanical properties, electrical properties, heat resistance, flame retardancy, and chemical stability. PPS / PPE alloys combine the advantages of both PPS and PPE, including high temperature resistance, flame retardancy, and chemical corrosion resistance, while overcoming the disadvantages of PPS such as brittleness, low melt viscosity, and difficulty in molding due to injection molding flash, as well as the disadvantages of PPE such as poor solvent resistance and excessive melt viscosity. However, PPS and PPE are incompatible polymers with a large viscosity difference. During mixing, there are no intermolecular forces between the molecular chain segments, resulting in uneven mixing and a very low elongation at break, making continuous extrusion molding impossible after mixing. Adding some conventional compatibilizers can improve compatibility, but due to insufficient compatibility, it can reduce the heat resistance of the material; or due to insufficient heat resistance, it can decompose during processing to produce carbides, forming carbonization points, resulting in poor quality of the extruded product.

[0003] Therefore, a PPS / PPE composite material with good heat resistance, high elongation at break, and few carbonization points has broad application prospects. Summary of the Invention

[0004] Based on this, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a PPS / PPE composite material with good heat resistance, high elongation at break and few carbonization points, as well as its preparation method and application.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a PPS / PPE composite material, comprising the following components in parts by weight: 50-90 parts of polyphenylene sulfide resin (PPS), 5-20 parts of polyphenylene sulfide resin (PPE), and 3-10 parts of graft copolymer; wherein the graft copolymer comprises a main chain and side chains, the main chain being one of polyethylene (PE), polypropylene (PP), ethylene copolymer, and propylene copolymer, and the side chains being one of polystyrene (PS) and styrene copolymer; the pH value of the polyphenylene sulfide resin is 5-8.

[0006] Preferably, the main chain of the graft copolymer is one of ethylene copolymer and propylene copolymer.

[0007] Preferably, the ethylene copolymer includes one of ethylene-glycidyl methacrylate (EGMA), ethylene-ethyl acrylate copolymer (EEA), and ethylene-butyl acrylate copolymer (EBA); the propylene copolymer includes one of propylene-glycidyl methacrylate (PGMA) and propylene-ethyl acrylate copolymer (PEA).

[0008] Preferably, the styrene copolymer includes one of styrene-acrylonitrile copolymer (AS) and styrene-acrylonitrile-glycidyl methacrylate copolymer (P(GMA / AS)).

[0009] Preferably, the graft copolymer is one of the following: a graft copolymer of main chain PE and side chain PS, a graft copolymer of main chain PE and side chain AS, a graft copolymer of main chain EBA and side chain PS, a graft copolymer of main chain PP and side chain AS, a graft copolymer of main chain EGMA and side chain PS, and a graft copolymer of main chain EEA and side chain AS.

[0010] Preferably, in the graft copolymer, the main chain accounts for 40-80% of the graft copolymer by mass, and the side chain accounts for 20-60% of the graft copolymer by mass; when the side chain is a styrene copolymer, acrylonitrile accounts for 30-80% of the styrene copolymer by mass, and styrene accounts for 20-70% of the styrene copolymer by mass.

[0011] Preferably, the method for testing the pH value of the polyphenylene sulfide resin is as follows: dissolve 50g of PPS resin in 500mL of aqueous solution, stir evenly, let stand for 30 minutes, and then test with a pH meter to obtain the pH value of the PPS resin.

[0012] Preferably, the weight percentage of the PPS resin in the PPS composite material is not less than 60%.

[0013] This invention uses graft copolymers with specific main chains and side chains, which can take into account both PPS and PPE components. It can effectively improve the compatibility of PPS / PPE and improve the elongation at break of the material while maintaining heat resistance. At the same time, the use of graft copolymers with specific main chains and side chains in this invention results in very few carbides generated during processing, and the quality of PPS / PPE alloy is better.

[0014] Optionally, the PPS resin is in the range of one or any two of the following weight parts: 50 parts, 51 parts, 53 parts, 55 parts, 58 parts, 60 parts, 61 parts, 63 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 80 parts, 82 parts, 85 parts, 88 parts, and 90 parts; the PPE resin is in the range of 5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, and 9 parts. The weight parts of the graft copolymer are within the range of one or any two of the following: 9.5 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts; the weight parts of the graft copolymer are within the range of one or any two of the following: 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, and 10 parts.

[0015] In actual experiments, the inventors discovered that when using a main chain of either ethylene copolymer or propylene copolymer, the specific flexible main chain can form a good entanglement with PPS resin and PPE resin, thereby significantly improving the compatibility effect even with a very low addition amount. This can better improve heat resistance and elongation at break, and reduce the carbonization point.

[0016] Preferably, the PPS / PPE composite material comprises the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene sulfide resin, and 5-8 parts of graft copolymer.

[0017] Preferably, the polyphenylene sulfide resin has a melt flow rate ≤300g / 10min under a test temperature of 316℃ and a load of 5kg according to ISO 1133-2022; the polyphenylene sulfide resin has a melt flow rate of 10-40g / 10min under a test temperature of 315℃ and a load of 10kg according to ISO 1133-2022; and the graft copolymer has a melt flow rate <2g / 10min under a test temperature of 190℃ and a load of 2.16kg according to ISO 1133-2022.

[0018] Optionally, the polyphenylene sulfide resin, according to ISO 1133-2022, under test conditions of 316°C and 5kg load, has a melt mass flow rate of one or any two of the following values: 300g / 10min, 280g / 10min, 250g / 10min, 200g / 10min, 150g / 10min, 130g / 10min, 100g / 10min, 80g / 10min, 70g / 10min, 60g / 10min, and 50g / 10min.

[0019] Optionally, the polyphenylene ether resin is specified according to ISO 1133-2022, with a melt mass flow rate of 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, or 40 g / 10 min under a test temperature of 315°C and a load of 10 kg, or any combination thereof.

[0020] Optionally, the graft copolymer is specified according to ISO 1133-2022, under test conditions of 190°C and 2.16 kg, with a melt mass flow rate of 1.8 g / 10 min, 1.5 g / 10 min, 1.3 g / 10 min, 1.2 g / 10 min, 1.0 g / 10 min, 0.8 g / 10 min, and 0.5 g / 10 min, or any two of these values.

[0021] Preferably, the PPS / PPE composite material further includes 0.1-3.5 parts of processing aids, wherein the processing aids are at least one of lubricant, colorant, and antioxidant.

[0022] Optionally, the antioxidant is 0.1-0.5 parts by weight, and the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants, such as antioxidant 168 (tris[2,4-di-tert-butylphenyl] phosphite) and antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]).

[0023] Optionally, the lubricant is 0.1-1 parts by weight, and the lubricant is at least one of stearates, stearates, and ethylene bis-stearamides, such as pentaerythritol stearate, zinc stearate, etc.

[0024] Optionally, the colorant is 0.1-2 parts by weight, and the colorant is at least one of zinc sulfide, carbon black, iron oxide red, titanium dioxide, and iron yellow.

[0025] Furthermore, the present invention provides a method for preparing the PPS / PPE composite material, comprising the following steps: mixing the components in proportion, performing melt extrusion, and granulation to obtain the PPS / PPE composite material.

[0026] Furthermore, the present invention provides the application of the aforementioned PPS / PPE composite material in the automotive field.

[0027] Specifically, the present invention provides the application of the aforementioned PPS / PPE composite material in the preparation of automotive extruded cooling pipes or extruded liquid cooling plates.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention selects graft copolymers with specific main chains and side chains, which can take into account both PPS and PPE components, and can very effectively improve the compatibility of PPS / PPE. It can also improve the elongation at break of the material while maintaining heat resistance. At the same time, the use of graft copolymers with specific main chains and side chains in the present invention results in very few carbides generated during processing, and the quality of PPS / PPE alloy is better. Detailed Implementation

[0029] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. The purpose is to provide a detailed understanding of the invention, not to limit it. All other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention. Unless otherwise specified, the experimental reagents and instruments designed in the embodiments and comparative examples of this invention are commonly used reagents and instruments, all of which are commercially available. Unless otherwise specified, the experimental methods used in the embodiments and comparative examples are conventional methods; and unless otherwise specified, the raw materials used in parallel experiments are from the same batch.

[0030] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0031] PPS-1: Melt flow rate 180g / 10min (316℃ / 5kg), manufacturer: Xinhecheng, grade: PPS-3418, pH value: 5.5;

[0032] PPS-2: Melt flow rate 150g / 10min (316℃ / 5kg), manufacturer: Binhua, grade: PPS-Q210, pH value: 6.8;

[0033] PPS-3: Melt flow rate 80g / 10min (316℃ / 5kg), manufacturer: Xinhecheng, grade: PPS 3508, pH value: 7.8;

[0034] PPS-4: Melt flow rate 350g / 10min (316℃ / 5kg), manufacturer: Tongling, grade: PPS 2035, pH value: 8.8

[0035] PPS-5: Melt flow rate 180g / 10min (316℃ / 5kg), manufacturer: Xinhecheng, grade: PPS3418HA, pH value: 4.3;

[0036] PPE-1: Melt flow rate 35g / 10min (315℃ / 10kg), Bluestar, grade PPE LXN040;

[0037] PPE-2: Melt flow rate 15g / 10min (315℃ / 10kg), Zhongmu, grade PPE ZM045;

[0038] Graft copolymer-1: Main chain PE, side chain PS, manufacturer: Nippon Oil Co., Ltd. A1100;

[0039] Graft copolymer-2: Main chain PE, side chain AS, manufacturer: Nippon Oil Co., Ltd. A1401;

[0040] Graft copolymer-3: main chain EBA, side chain PS, manufacturer GRAFT POLYMER, GRAFTALLOY EB-PS;

[0041] Graft copolymer-4: Main chain PP, side chain AS, Nippon Yusen Co., Ltd. A3400;

[0042] Graft copolymer-5: Main chain EGMA, side chain PS, Nippon Oil Co., Ltd. A4100;

[0043] Graft copolymer-6: main chain EEA, side chain AS, Nippon Yusen Co., Ltd. A5400;

[0044] Graft copolymer-7: Main chain PC, side chain PS, Nippon Yusen Co., Ltd. CL130D;

[0045] Styrene-GMA copolymer: Styrene-GMA copolymer, manufacturer: Jia Yi Rong, grade: SG-06;

[0046] SEBS-g-MAH: Manufacturer: Kertész, Grade: SEBS FG1901 G;

[0047] The antioxidant is a compound of commercially available hindered phenolic antioxidant 1010 and commercially available phosphite antioxidant 168 in a mass ratio of 1:1.

[0048] The lubricant is pentaerythritol stearate, which is commercially available.

[0049] Examples 1-12 and Comparative Examples 1-7

[0050] The PPS / PPE composite material of the present invention has the following composition as shown in Tables 1 and 2. The preparation method of the PPS / PPE composite material includes the following steps:

[0051] The components are mixed in proportion, melt-extruded through a twin-screw extruder, and granulated to obtain the PPS / PPE composite material; the screw temperature of each section of the twin-screw extruder is 220-320℃.

[0052] Performance testing

[0053] Testing standards:

[0054] Heat distortion temperature: Test standard ISO 75-2-2013, test condition 1.8MPa.

[0055] Elongation at break: Test standard ISO 527-2-2012, test conditions 50 mm / min, 23℃.

[0056] Evaluation of carbonization points during extrusion molding: The PPS / PPE composite materials prepared in the embodiments and comparative examples of this invention were injected into a Hacker rheometer and extruded into PPS hollow pipes. After continuous extrusion for 1 minute, 1 m of pipe was collected and the number of carbonization points on the pipe surface was observed.

[0057] The test results are shown in Table 1-2.

[0058] Table 1

[0059]

[0060]

[0061] Table 2

[0062]

[0063] As shown in the table above, the PPS / PPE composite material prepared in the embodiments of the present invention has a heat distortion temperature >105℃, an elongation at break >30%, and ≤2 carbonization points.

[0064] As can be seen from the comparison of Examples 1, 6-9, and Comparative Examples 1-4, the graft copolymers of specific main chains and side chains used in this invention can balance the properties of both PPS and PPE components, effectively improving the compatibility of PPS / PPE. It also increases the elongation at break of the material while maintaining heat resistance. Furthermore, the use of graft copolymers of specific main chains and side chains in this invention results in very few carbides generated during processing, leading to better quality PPS / PPE alloys. When the main chain is either an ethylene copolymer or a propylene copolymer, the elongation at break is even higher, and the heat resistance is even better.

[0065] Comparative Example 1 used a graft copolymer-7 with PC as the main chain and PS as the side chain. When the main chain of the graft copolymer is polycarbonate (PC), it cannot form effective entanglement with the segments of PPS and PPE, thus worsening the elongation. Comparative Example 2 used a styrene-GMA copolymer, which exhibited excessive entanglement with the segments of PPS and PPE, also worsening the elongation. Comparative Example 3 used SEBS-g-MAH, resulting in a significant decrease in heat resistance. Furthermore, the elastomer itself lacked sufficient heat resistance, leading to carbonization during production.

[0066] As can be seen from the comparison of Examples 1, 10-12 and Comparative Example 5, when the PPS / PPE composite material includes the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene sulfide resin and 5-8 parts of graft copolymer, the heat distortion temperature is higher, the elongation at break is greater and the number of carbonization points is less.

[0067] As can be seen from the comparison of Examples 1-3 and Comparative Examples 6-7, when the pH value of the polyphenylene sulfide resin is 5-8, the heat distortion temperature is higher, the elongation at break is greater, and the number of carbonization points is less.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A PPS / PPE composite material, characterized in that, It includes the following components in parts by weight: 70-90 parts of polyphenylene sulfide resin, 5-15 parts of polyphenylene sulfide resin, and 3-10 parts of graft copolymer. The graft copolymer comprises a main chain and side chains, wherein the main chain is one of polyethylene, polypropylene, ethylene copolymer, and propylene copolymer, and the side chains are one of polystyrene and styrene copolymer; the pH value of the polyphenylene sulfide resin is 5-8.

2. The PPS / PPE composite material as described in claim 1, characterized in that, The main chain of the graft copolymer is one of ethylene copolymer and propylene copolymer.

3. The PPS / PPE composite material as described in claim 1 or 2, characterized in that, The ethylene copolymer includes one of ethylene-glycidyl methacrylate, ethylene-ethyl acrylate copolymer, and ethylene-butyl acrylate copolymer, and the propylene copolymer includes one of propylene-glycidyl methacrylate and propylene-ethyl acrylate copolymer.

4. The PPS / PPE composite material as described in claim 1, characterized in that, The styrene copolymer includes one of styrene-acrylonitrile copolymer and styrene-acrylonitrile-glycidyl methacrylate copolymer.

5. The PPS / PPE composite material as described in claim 1, characterized in that, It includes the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene sulfide resin, and 5-8 parts of graft copolymer.

6. The PPS / PPE composite material as described in claim 1, characterized in that, The polyphenylene sulfide resin, according to ISO 1133-2022, has a melt flow rate ≤300 g / 10 min at a test temperature of 316°C and a load of 5 kg; the polyphenylene sulfide resin, according to ISO 1133-2022, has a melt flow rate of 10-40 g / 10 min at a test temperature of 315°C and a load of 10 kg; the graft copolymer, according to ISO 1133-2022, has a melt flow rate <2 g / 10 min at a test temperature of 190°C and a load of 2.16 kg.

7. The PPS / PPE composite material as described in claim 1, characterized in that, The PPS / PPE composite material also includes 0.1-3.5 parts of processing aids, wherein the processing aids are at least one of lubricant, colorant, and antioxidant.

8. A method for preparing the PPS / PPE composite material according to any one of claims 1-7, characterized in that, Includes the following steps: The components are mixed in proportion, melt extruded, and granulated to obtain the PPS / PPE composite material.

9. The application of a PPS / PPE composite material as described in any one of claims 1-7 in the automotive field.

10. The application of a PPS / PPE composite material as described in any one of claims 1-7 in the preparation of automotive extruded cooling pipes or extruded liquid cooling plates.

Citation Information

Patent Citations

  • Extruded and rolled polyphenylene sulfide copper-clad plate material and preparation method thereof

    CN114106558A

  • Polyphenylene ether-containing resin composition and method of producing the same

    JP2012224754A